3D printed prosthetic hand with grasping and slippage detection for children - Devin, Babu (2024)
This study focuses on the creation and assessment of a children-specific functioning 1 Degree of Freedom (DOF) 3D-printed prosthetic hand. For people with upper limb problems, prosthetic hands are essential for aiding daily activities. However, a lot of current prosthetic hands are unable to change grasping force independently of visual input. This research addresses three primary objectives. Firstly, it aims to create a functional prosthetic hand-tailored for pediatric users. Secondly, it seeks to assess the prosthetic hand's grasping force across various objects. Finally, the research endeavours to implement strategies to reduce slippage by regulating grasping force. Three distinct objects—a 54g puzzle piece, a 107g miniature book, and a 3g plastic ball—were used in the experiment. The findings showed that object attributes had a substantial impact on considerable variations in force application. Due to the material properties of plastic, wooden things required less force than they did. Furthermore, manipulating things with irregular shapes requires more effort. Precision grasps were outperformed in terms of force application by power grasps that offered full contact. Consistently, cylindrical objects showed lower forces, indicating ergonomic difficulties with holding non-uniform shapes. These insights are essential for developing tools and interfaces that are user-interactive and usable, particularly in the creation of robotics and ergonomic equipment. The study also projects how prosthetic technology will evolve in the future. Individual motorized fingers with many degrees of articulation are implemented as well as cuttingedge sensing technologies like muscle or brain sensors. To evaluate the strength of the prosthetic hand, the research aims to investigate a wide variety of 3D printing materials. Incorporating a complete glove force sensor will also make it possible to measure opposing forces precisely while performing gripping and lifting duties. Our comprehension of material-specific gripping dynamics and slippage tendencies will be further improved by a thorough examination of numerous objects made of different materials. The goal of this research is to dramatically increase the usability and adaptability of prosthetic systems.